Pengaruh Motivasi Kerja dan Disiplin Kerja terhadap Kinerja Karyawan - Muhammad Hasby Hasbunallah; Kasbuntoro Kasbuntoro; Pawit Winarto; Sari Maemunah (Journal of Accounting, Management, and Economics Research (JAMER), 2024)
Motivation is among the elements that can help achieve peak performance. Managers use work discipline as a technique to talk to staff members and get their cooperation in changing their conduct. It also raises knowledge of corporate policies and social norms and encourages people to follow them. The purpose of this thesis is to ascertain and examine how work discipline and motivation affect the output of PT employees. Auto Technology Indonesia. Researchers used a convenience sampling technique, this technique determines the sample based on all employees of PT. Auto Teknologi Indonesia Motivation research results have a major impact on PT Auto Teknologi employees' performance. At PT Auto Teknologi Indonesia, the results of discipline tests have a big impact on employee performance. The outcomes of evaluating Work Discipline and Motivation at the same time have a major impact on Employee Performance. Managerial implications: Giving regular awards or recognition to employees who demonstrate good performance can increase their motivation. Carrying out routine monitoring and performance evaluations to ensure employees comply with established disciplinary standards.